(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research discussed and analyzed the formulation of a strategy to manage tax compliance risks, as an applied research in the General commission for Taxes. The questionnaire was used as a research tool to identify the factors that stimulate or retard the research sample from being compliant. The K-means clustering method was also used to enable the classification of the research sample’s views into four behaviors, some of these views pose tax-compliance risks. The research concluded that risk management is a continuous process and that all departments of the General commission for Taxes are responsible for its implementation to enable them to deal with the behavior of the taxpayer towards tax compliance. And it recommended the adoption of a strategy to manage these behaviors, which represent the risk of tax compliance by the General commission of Taxes, to reach the level that achieves the highest voluntary compliance.